Cine (Trans) nacional: festivales de cine y marcas de identidad - Carolina Soria (Nuevo mundo - Mundos Nuevos, 2016)
This article aims to reflect on the scope and limitations of the concept of "national cinema" today. The last decade saw the emergence of numerous film studies that put the spotlight on to that concept, questioning to phenomena such as globalization, multiculturalism and hybridization, as well as facing new ways of coproduction and exhibition whose epicenter at film festivals. This situation has led researchers to propose the concept of "transnational cinema" as a new way of understanding cinema in its global dimension. The analysis of the national/transnational dichotomy and the reflection on film festivals as creators of identity brands will focus on recent Argentine cinema, taking into account the coproduction market Buenos Aires Lab (BAL).